Manajemen Perpustakaan dalam Meningkatkan Minat Baca Siswa - Hendra Purwanto; Suharyanto H. Soro (Global Education Journal, 2026)
School libraries are a crucial component of the elementary education ecosystem, serving as learning resource centers, information centers, and drivers of literacy culture. However, library management at the elementary school level often faces classic obstacles, ranging from limited collection variety, inadequate facilities, low student visits, and suboptimal management amidst the challenges of digital device disruption. This study aims to describe and analyze in depth library management, including aspects of planning, organizing, implementing, and controlling, in order to increase student reading interest. Furthermore, this study identifies supporting and inhibiting factors that influence the effectiveness of library management. This study uses a qualitative case study approach. Data collection was conducted through participatory observation of physical conditions and services, interviews with the principal, library managers, teachers, and students, and documentation studies. Data analysis techniques were carried out interactively through the stages of data reduction, data presentation, and conclusion drawing and verification. The results show that effective and systematic library management contributes significantly to increasing student reading interest. The conclusion of this research is that inclusive and well-organized library management not only fulfills physical comfort (aesthetic value) but also stimulates students to build knowledge independently (constructivism principle).